(Un)stable Ghettos: The Current State of the History of Jewry in Early Modern Italy - Di Nepi, Serena (Church history and religious culture, 2024)
This article reviews Italian and international historiography on the history of Jews in Italy during the early modern period, aiming to critically engage with the notion of the “ghetto” and the interpretive frameworks through which it has been studied. It situates this concept within broader historiographical trends in Italian history of the period. The study gives particular attention to the growing influence of the Roman Inquisition and its pervasive—though not total—control over Jewish communities, noting the varied ways this influence was enacted across Italy’s diverse urban and rural regions. The analysis begins with an exploration of Jewish responses to the temporary readmission into the Papal States under Pope Sixtus V from 1587 to 1590, using this episode to re-evaluate the category of the ghetto. The conclusion argues for a future research direction that moves beyond the assumed stability of the ghetto, reconstructing the history of Jews in Italy by identifying people, places, actors, distinctions, and movements—while remaining mindful of the profound impact of the long history of persecutions.